NOVEL PAJANG KARYA WAWAN SUSETYA SEBAGAI MATERI PEMBELAJARAN SASTRA: SOSIOLOGI SASTRA DAN NILAI PENDIDIKAN KARAKTER - Ridho Aji Perdana; Herman J Waluyo; Budi Waluyo (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2019)
This research  aims to explain: (1) social background of Pajang  novel writer; (2) the sociological background of Pajang  novel by Wawan Susetya; (3) readers' responses to Pajang's novel by Wawan Susetya; (4) the value of character education contained in Pajang's novel by Wawan Susetya; and (5) the relevance of Pajang's  novel by Wawan Susetya as a literary learning material in high school. This research uses descriptive qualitative method and using a study of sociology of literature. The result of this research is description about: (1) social background of Pajang novel writer covering aspect of race, moment (moment), and environment (milieu); (2) Sociological background of Pajang's work by Wawan Susetya includes social  group,  culture,  social  institution, stratification, and  power;  (3) readers' responses  to  Pajang's  novel by  Wawan Susetya;  (4)  the  value  of  character education contained in the Pajang  novel by Wawan Susetya include religious, tolerance, hard work, democratic, curiosity, nationalism, achievement, friendly / communicative, social, and responsibility; (5) the relevance of Pajang's  novel by Wawan Susetya as a literary learning material in Senior High School which is adapted to the content aspect, presentation aspect, language aspect, and graphictions aspect.